Efficacy of indoor air purification in treating Artemisia (mugwort) pollen allergic rhinitis: study protocol for a randomised controlled trial - Qiao-yan Chen; Li Li; Li Zhang; Jin-han Mo; Zi-feng Yang; Xiao-lin Wei; Yun-ying Li; Ji-yan Xia; Xiao-bing Bai; Pei-fang Xie (BMC Public Health, 2018)
Abstract Background Allergic rhinitis (AR) is a worldwide health problem. Allergen avoidance is strongly recommended for AR patients. Air purification can reduce concentrations of particles in indoor air, including those of allergens. Air purifiers have been recommended by clinicians for AR patients, but few studies have focused on the removal of airborne allergens from home environments. Such studies have been limited by a lack of blinding, small samples, or a failure to measure allergen levels, disease activity, or a combination of these factors. This study investigates the efficacy of a high-efficiency air purifier in reducing disease activity in the homes of AR patients sensitive to the allergens produced by Artemisia (mugwort) pollen. Methods This is a randomized, double-blind, clinical controlled trial that will test active and inactive versions of an air purifier (Atmosphere®; Amway China). Sixty AR patients sensitive to the allergens produced by Artemisia pollen will be assigned randomly to two groups of equal numbers. All patients will undergo a 4-week treatment period and a 4-week observation period. Evaluation will be conducted at baseline (day 0) and on days 7, 14, 21, 28, and 56. The primary outcome measure will be the difference in visual analog scale scores from baseline. Secondary outcomes will be changes from baseline in nasal symptoms, allergy symptom scores, responses to the Rhinoconjunctivitis Quality of Life Questionnaire, Epworth Sleepiness Scale scores, and tolerability scores for the air purifier. Side effects of treatment will be recorded. Discussion Reducing exposure to allergens can reduce the risk of conditions such as AR. We hypothesise that AR patients sensitive to the allergens produced by Artemisia pollen will not suffer symptoms in a pollen-free environment. AR patients can remove pollen from their homes using air purifiers, decreasing the risk of symptoms. We expect that our study results will provide reliable evidence for determining the effects of air-purification therapy. Trial registration ChiCTR-INR-17012481. (Retrospectively registered 26 August 2017).